"The impact of strategic direction on product development, an applied study on Premier Food Products "Khartoum-2022 - Mohamed, Eshraga Abdullah (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of strategic direction (creative and proactive) on product development by applying it to Premier Food Products Company and to know the trends of the sample members on the relationship between creative and proactive strategic direction and product development. Proactively developing the products of Premier Food Products. The study has importance on both the theoretical and practical levels. The study dealt with two hypotheses to find out the existence of a statistically significant relationship between strategic orientation (creative and proactive) and product development. To achieve the objectives of the study, the descriptive analytical approach was used, and a questionnaire was designed and used as a tool for data collection.) A random sample of the study population was selected, numbering (30) employees with different job titles, representing 25% of the community size. The statistical analysis program SPSS was used for analysis. A number of results were also reached, the most important of which is that the correlation coefficient between product development and creative strategic direction was (0.66), with a positive sign, and its probabilistic value (0.000), which is less than the level of significance (0.05), which means that there is a direct statistically significant relationship between product development and orientation Creative strategist. And the correlation coefficient between product development and proactive strategic direction was (0.68), with a positive sign, and its probabilistic value (0.000) which is less than the level of significance (0.05), which means that there is a direct statistically significant relationship between product development and proactive strategic direction.Based on the mentioned results, the study recommended paying attention to motivating employees who have creative ideas to benefit from their ideas in developing the company's products. The study also recommended paying attention to competitors and constantly monitoring them to develop the appropriate strategy capable of facing competition.
Keywords: creative strategic direction; proactive strategic direction; product development